Against the odds: Teaching writing in an online environment - Wijeyewardene, Ingrid; Patterson, Helen; Collins, Martin (Journal of Academic Language and Learning, 2013)
This paper outlines an approach to teaching academic writing in an online mode. The Pathways Enabling Course at the University of New England (UNE) was launched in 2008 and has provided us with a cohort of students from educationally disadvantaged backgrounds who often lack the social capital necessary to write successfully in an academic context. These academic literacy units have been developed and taught by Academic Language and Learning (ALL) staff at UNE. As the Pathways students are external, there is a danger that they will not engage with the unit content and learning environment. The challenge has been to adapt writing pedagogy to the online environment, subject to the constraints of the tools that are available in the learning management system (Moodle). In the five years that this program has been offered, we have developed some key strategies that provide appropriate, scaffolded teaching and learning activities to develop academic writing in the online environment. This involves the innovative use of the available tools to successfully engage students in writing activities. Our primary teaching tools included Moodle’s database activity, which we integrated with other online activities to generate substantial student engagement, participation and interactivity. We believe our approach offers a valuable opportunity for ALL professionals and students to interact online, producing written work that can be shaped through corrective feedback and redrafting. We present some samples of student work and show how, with appropriate feedback and learning resources, students can develop their proficiency in academic writing to improve their chances of academic success.